Sosialisasi dan Pelatihan Pemanfaatan Sampah Anorganik Menjadi Media Tanam Vertikultur pada Masyarakat di Gili Air - Sukartono Sukartono; Siska Ita Selvia; Lalu Arifin Aria Bakti; Bambang Hari Kusumo; Suwardji Suwardji (Universitas Mataram, 2023)
Gili Air as one of the Small Islands in West Nusa Tenggara (NTB) has various geographical limitations and even has economic dependence on the tourism industry. The large number of tourists has an impact on the amount of waste generated every day. This is not balanced with optimal waste management in Gili Air, where waste from each household and tourism supporting facilities is just piled up, then taken by the transportation service (Gili Care) and disposed of in the TPA (Final Disposal Site) in Lombok Big Island. Waste management on Gili Air requires a large amount of money because you have to pay for transportation by boat. Some local people and owners of tourism-supporting facilities manage their waste by dumping it in pits or burning it. Some of them who know the economic value of inorganic waste sell directly cardboard, used bottles, iron and others to collectors or scavengers themselves. The waste bank in Gili Air has not run optimally, so the reduction in waste generation only comes from selling used goods individually. Based on these various problems, the service team carried out community service activities through outreach and training on the use of inorganic waste to become verticultural planting media which indirectly contributed to household-scale greening in Gili Air. The goal of this activity is to generate enthusiasm and participation from Karang Taruna Gili Air (KTGA) in terms of waste management. This service activity took place enthusiastically and actively involved KTGA, where the evaluation results showed that there was an increase in knowledge of 47%. The community's activeness in providing questions and responses is an asset for participatory community empowerment in Gili Air.